Advances in Synthetic Biology and Biosafety Governance - Li, Jing; Zhao, Huimiao; Zheng, Lanxin; An, Wenlin (Frontiers in Bioengineering and Biotechnology, 2021)
Tremendous advances in the field of synthetic biology have been witnessed in multiple areas including life sciences, industrial development, and environmental bio-remediation. However, due to the limitations of human understanding in the code of life, any possible intended or unintended uses of synthetic biology, and other unknown reasons, the development and application of this technology has raised concerns over biosafety, biosecurity and even cyberbiosecurity that they may expose public health and the environment to unknown hazards. Over the past decades, some countries in Europe, America and Asia have enacted laws and regulations to control the application of synthetic biology techniques in basic and applied research and this has resulted in some benefits. The outbreak of the COVID-19 caused by novel coronavirus SARS-CoV-2 and various speculations about the origin of this virus have attracted more attention on bio-risk concerns of synthetic biology because of its potential power and uncertainty in the synthesis and engineering of living organisms. Therefore, it is crucial to scrutinize the control measures put in place to ensure appropriate use, promote the development of synthetic biology, and strengthen the governance of pathogen-related research, although the true origin of coronavirus remains hotly debated and unresolved. This article reviews the recent progress made in the field of synthetic biology and combs laws and regulations in governing bio-risk issues. We emphasize the urgent need for legislative and regulatory constraints and oversight to address the biological risks of synthetic biology.